The convergence between evolutionary biology and social sciences - Costa Filho, Geraldo Pedro da (2019)
This article’s aims are to retrace the attempts to bring evolutionary biology closer to the social sciences by identifying the obstacles that arose at the beginning of the consolidation of biology and sociology as sciences in the nineteenth century and the affinities between them, revealed through concepts such as organism and evolution, developed throughout the twentieth century by both sociology and biology.